Alliance of civilizations: the global peace project of the 21st Century - Demirel, Serdar (USA, David Publishing Company, 2010)
The Alliance of Civilizations was established in 2005, at the initiative of the Governments of Spain and Turkey; under the auspices of the United Nations for inter civilizations dialogue to bridge the gap between the West and Muslim world. This article analyzes advantage and disadvantage sides of the success of this initiative.